I have a discrete uniform distribution (from IFoA formulae) with parameters a, b, h, where a and b are the start/end points, and h is the interval between each value. The p.d.f. is given as $\frac{h}{b-a+h}$. I manage to find out $$E[X] = \sum_{x\in X} xf(x) = \sum_{x\in X} \frac{xh}{b-a+h} = \frac{h}{b-a+h}\sum_{x\in X} x\\= \frac{h}{b-a+h}\times \frac{a+b}{2}\times \frac{b-a+h}{h} = \frac{a+b}{2}.$$ However, I cannot figure out the second moment ($E[X^2]$) and Variance by using the same method. I wonder if it is possible to find them using the same way, I know they could be found by using the M.G.F., I just want to know if it is possible.

$Var(X) = \frac{(b-a)(b-a+2h)}{12}$ is given by the formulae.

Here is what I have got so far: $$\sum_{x\in X} x^2f(x) = \sum_{x\in X} \frac{x^2 h}{b-a+h} = \frac{h}{b-a+h}\sum_{x\in X} x^2=\frac{h}{b-a+h}\sum_{k=0}^{\frac{b-a+h}{h}}(hk+a)^2$$

edit: \begin{align*} E[X^2] &= \sum_{x\in X} x^2f(x)\\ &=\frac{h^3}{b-a+h}\sum_{k=0}^{\frac{b-a+h}{h}}k^2+\frac{2ah^2}{b-a+h}\sum_{k=0}^{\frac{b-a+h}{h}}k+\frac{a^2h}{b-a+h}\sum_{k=0}^{\frac{b-a+h}{h}}1\\ &=\frac{h^3}{b-a+h}\frac{(\frac{b-a}{h})(\frac{b-a}{h}+1)(2(\frac{b-a}{h})+1)}{6}+\frac{2ah^2}{b-a+h}\frac{(\frac{b-a}{h}+1)(\frac{b-a}{h})}{2}+\frac{a^2h}{b-a+h}\bigg(\frac{b-a}{h}+1\bigg)\\ &= \frac{h^3}{b-a+h}\frac{(\frac{b-a}{h})(\frac{b-a+h}{h})(\frac{2(b-a)+h}{h})}{6}+\frac{2ah^2}{b-a+h}\frac{(\frac{b-a+h}{h})(\frac{b-a}{h})}{2}+\frac{a^2h}{b-a+h}\bigg(\frac{b-a+h}{h}\bigg)\\ &= \frac{(b-a)(2(b-a)+h)}{6}+a(b-a)+a^2\\ Var(X) &= E[X^2] - E[X]^2\\ &= \frac{(b-a)(2(b-a)+h)}{6}+a(b-a)+a^2 - \bigg(\frac{a+b}{2}\bigg)^2\\ &= \frac{2(b-a)(2(b-a)+h)+12a(b-a)+12a^2}{12} - \frac{3(a+b)^2}{12}\\ &= \frac{4b^2-4ab+2bh-4ab+4a^2-2ah+12ab-12a^2+12a^2-3a^2-6ab-3b^2}{12}\\ &= \frac{(a-b)^2+2h(b-a)}{12} \\ &= \frac{(b-a)^2+2h(b-a)}{12}\\ &= \frac{(b-a)(b-a+2h)}{12} \end{align*}

  • $\begingroup$ Would it help if you knew that $\sum_{x=0}^n x^2 = \frac{n(n+1)(2n+1)}{6}$? $\endgroup$ – Paul Oct 2 '18 at 14:33
  • $\begingroup$ It would be helpful for $h = 1$, but I cannot imply it for $h\neq1$. $\endgroup$ – VincentN Oct 2 '18 at 14:36
  • $\begingroup$ You can apply it for $x'=x/h$. $\endgroup$ – Paul Oct 2 '18 at 14:38
  • $\begingroup$ I don't quite get what you mean by that. $\endgroup$ – VincentN Oct 2 '18 at 14:53
  • $\begingroup$ I'll put it in an answer. $\endgroup$ – Paul Oct 2 '18 at 14:57

With your edit, you are almost there. You can simplify $$\frac{h}{b-a+h}\sum_{k=0}^{b-a}(hk+a)^2$$ $$=\frac{h}{b-a+h}\sum_{k=0}^{b-a}\left((hk)^2+2ahk+a^2 \right)$$ $$=\frac{h}{b-a+h}\sum_{k=0}^{b-a}(hk)^2+\frac{h}{b-a+h}\sum_{k=0}^{b-a}(2ahk)+\frac{h}{b-a+h}\sum_{k=0}^{b-a}a^2$$ $$=\frac{h^3}{b-a+h}\sum_{k=0}^{b-a}k^2+\frac{2ah^2}{b-a+h}\sum_{k=0}^{b-a}k+\frac{a^2h}{b-a+h}\sum_{k=0}^{b-a}1$$ For the first term you can apply $$\sum_{x=0}^n x^2 = \frac{n(n+1)(2n+1)}{6}$$ and apply the similar formulas that you did previously for the other 2 terms.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.